Development of an IoT-Based Digital Measuring Instrument Training Kit as an Interactive Learning Tool to Boost Students’ Interest in Learning - Nursina Sari; Linda Sekar Utami (IJECA (International Journal of Education and Curriculum Application), 2026)
This  study developed an IoT-based digital measuring instrument training kit to enhance the learning motivation of students on the Primary School Teacher Education programme. Given that practical activities relating to measurement in the ‘Basic Concepts of Primary School Physics’ course are still considered challenging, and that the integration of digital technology into teaching remains limited, this IoT-based training kit is designed to bridge the gap between theory and practice. This research is a research and development (R&D) study that adapts the Borg and Gall model, applied in a pilot study and a large-scale trial at the PGSD UMMAT. Data were collected using an expert validation questionnaire, a student response questionnaire, and a learning interest questionnaire, and were subsequently analysed using a paired sample t-test, N=Gain, and descriptive statistics. The validation results indicated a feasibility level of 84.94%, categorised  as ‘highly feasible’. The practicality test yielded an average score of 3.62, representing 72.4% in the ‘practical’ category. Statistical analysis using a paired-sample t-test revealed a significant difference between learning interest scores before and after the intervention (Sig. 0.000 < 0.05). The N-gain value of 0.54 falls into the moderate category. The use of an IoT-based digital measuring instrument training kit significantly increased active engagement and improved students’ ability to use IoT-based digital measuring instruments during practical learning activities, whilst also aiding their understanding of measurement concepts, thereby demonstrating that the use of modern measuring instruments is effective in boosting the learning interest of Primary School Teacher Education (PGSD) students.